Compliant three-dimensional thermoelectric generator filled with porous PDMS for power generation and solid-state cooling. (August 2021) - Zhang, Linli; Han, Xue; Du, Minzhi; Shi, Yulong; Zhang, Kun
Abstract: Due to the mutual conversion of heat and electricity, thermoelectric devices (TEDs) have an outstanding display in the field of wearable electronics and human body temperature regulation. However, their rigidity affects their wearing comfort. In this paper, combined with finite element analysis (FEA), we present a flexible TED, which uses porous PDMS with low thermal conductivity to replace organic elastomer to fill thermoelectric (TE) pillars connected with liquid metal. Our design provides a method to reduce the heat transfer through TEDs. The optimal power density of 2.33 μW cm -2 can be obtained under the natural convection. And with an applied Δ T of 8.8 K, a power density of 27.02 μW cm -2 can be achieved. Moreover, at applied current of 1.0 A, the cooling effect of the flexible TED can reach up to 7 K under natural convection and 2.8 K on human wrist under 1-sun (1 kW m -2 ) irradiation. Graphical abstract: Image 1 Highlights: TED filled with the porous PDMS substrate with low thermal conductivity (1.0 W m -1  K -1 ). The optimal power density of 27.02 μW cm -2 with an applied Δ T of 8.8 K. The maximum cooling effect can reach up to 7 K under natural convection. On human wrist, the optimal power density of 2.33 μW cm -2 . The cooling effect of 2.8 K can be achieved under 1 kW m -2 irradiation.